2020
DOI: 10.1111/eci.13201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifidobacterium longum BB536 and Lactobacillus rhamnosus HN001 in IBS patients

Abstract: Background Irritable bowel syndrome (IBS) is a common gastrointestinal disorder, which still lacks effective therapy. We aimed to investigate the effects of a novel formulation of Bifidobacterium longum BB536 and Lactobacillus rhamnosus HN001 with vitamin B6 (LBB) on symptoms, intestinal permeability, cultivable bacteria and metabolome in IBS subjects. Materials and methods Twenty‐five IBS patients (Rome IV criteria) (M:F = 8:17; age 48 years ± 11 SD) were randomized to treatment (LBB) or placebo (one month ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 41 publications
2
51
0
2
Order By: Relevance
“…These aspects should be specifically explored in future studies linking the role of gut microbiome and bacterial products, with local effects on the dynamics of epithelial barriers, and therefore intestinal permeability. Notably, in irritable bowel syndrome (IBS) patients, we recently found that oral administration of Bifidobacterium longum BB536 and Lactobacillus rhamnosus HN001 with vitamin B6 improved symptoms, severity of disease, while restoring intestinal permeability, modifying the composition of gut microbiota [59].…”
Section: Discussionmentioning
confidence: 99%
“…These aspects should be specifically explored in future studies linking the role of gut microbiome and bacterial products, with local effects on the dynamics of epithelial barriers, and therefore intestinal permeability. Notably, in irritable bowel syndrome (IBS) patients, we recently found that oral administration of Bifidobacterium longum BB536 and Lactobacillus rhamnosus HN001 with vitamin B6 improved symptoms, severity of disease, while restoring intestinal permeability, modifying the composition of gut microbiota [59].…”
Section: Discussionmentioning
confidence: 99%
“…48 Bifidobacterium longum BB536 and Lactobacillus rhamnosus HN001 restored intestinal permeability and gut microbiota in IBS patients. 49 Prevotella had a negative association with pain in IBS patients. 24 Clostridium sensu stricto 1 was a representative species of Clostridium and could produce short-chain fatty acids (SCFAs).…”
Section: Discussionmentioning
confidence: 90%
“…A likely explanation for these findings could lie in a prolonged period of exposure to PAMPs. More recently, it has been reported that treatment with B. longum BB536 and Lactobacillus rhamnosus HN001 with vitamin B6, compared to placebo, significantly improved GI symptoms and restored intestinal permeability in patients with IBS, as deduced by the improved percentage of sucralose recovery [53]. To date, very few studies have investigated serum zonulin concentration in patients with IBS.…”
Section: Discussionmentioning
confidence: 99%